Factors associated with chronic musculoskeletal pain in Japanese community-dwelling older adults: A cross-sectional study. Issue 23 (June 2017) - Hirase, Tatsuya; Kataoka, Hideki; Inokuchi, Shigeru; Nakano, Jiro; Sakamoto, Junya; Okita, Minoru
Abstract : Abstract: Identifying older adults with chronic musculoskeletal pain (CMP) earlier is urgent because CMP is reportedly associated with deterioration in physical function, poor psychological status, and low physical activity level. The objective of this study was to identify factors that were most strongly associated with CMP in Japanese community-dwelling older adults. Using a cross-sectional design, we assessed 263 older adults (mean age = 79.1 ± 5.9 years, 85.9% women) who participated in community exercise classes. Participants' physical function, psychological status, and activity levels were evaluated as outcome measures using a variety of tests and instruments. These assessments were conducted prior to beginning the exercise intervention program and compared participants with and without CMP. Additionally, relevant participant characteristics were collected and analyzed. In this study, CMP was defined as the presence of related symptoms within the past month that continued for at least 6 months and corresponded to a numerical rating scale of at least 5 or more at the site of maximum pain. A total of 143 (54.4%) participants met the criteria for CMP, and a high number of them had chronic lower back pain (64.3%). Outcome measures for the CMP group were significantly worse than for the non-CMP group ( P  < .05). Logistic regression analysis revealed that the Pain Catastrophizing Scale helplessness domain scores (odds ratio: 1.20, 95% confidence interval: 1.09–1.32) with an estimated value of 10 points was the factor most significantly associated with the presence of CMP. These findings suggest that assessment of the helplessness associated with pain-related catastrophizing is important for identification and the creation of interventions for older adults with CMP.